PENGARUH PEMAKAIAN KONTRASEPSI ORAL LEBIH DARI 3 TAHUN TERHADAP KADAR GULA DARAH - Solihah, Riyadatus; Haris, M.Shofwan (NHM PRESS, 2020)
Hormonal contraception is a contraceptive containing estrogen and progesterone hormones. The hormone affects blood glucose levels. The user of the hormonal contraceptive pill in Bangkalan in the year of 2017 as many as 22.64%, 37.36% injection, and implant 24.62%. The purpose of the study was to determine relation of hormonal contraception user with blood glucose. This research employed an analytic observational with cross-sectional design by using purposive sampling technique which involved 30 respondents from 97 population. The result of research shows that there is no relation between pill contraceptive users with blood glucose level p = 1.000 (α> 0.05), relation of contraceptive injection user with blood glucose level p = 0.05 (α <0.05) no relation of implant contraceptive user with blood glucose level p = 1.000 (α>0.05) based on Chi-Square test. Thus, it is concluded that there is a significant relationship between users of hormonal contraceptives with blood glucose levels in BPM Bu Yuni. In the future, it is suggested to do further research by controlling confounding variables influencing lifestyle, diet, and descendant.